A qualitative exploration of the views of patients and their relatives regarding interventions to minimize the distress related to postoperative delirium. (5th December 2019) - Meilak, Catherine; Biswell, Elizabeth; Willis, Rosalind; Partridge, Judith; Dhesi, Jugdeep
Abstract : Background: Postoperative delirium (POD) is common in older people and can be distressing for patients and their relatives. This study aimed to describe the experience of postoperative delirium and explore the views of patients and relatives in order to inform the codesign of an intervention to minimize distress related to postoperative delirium. Methods: Qualitative study using a thematic analysis of semistructured interviews in patients (n = 11) and relatives (n = 12) who experienced and witnessed POD, respectively. Results: Patients and relatives find POD distressing and desire information on the cause and consequences of delirium. This information should be delivered pre‐emptively where possible for patients and relatives during the episode for relatives and in post episode follow up for patients and their families. Information should be provided in person by a health care professional who has experience in managing delirium, supplemented by written materials. In addition, participants suggested training to improve staff and public awareness of delirium. Conclusions: This qualitative study showed that patients and relatives find delirium distressing, report the need for an intervention to minimize this distress, and enabled codesign of a pilot intervention. Refinement and evaluation of this intervention should form the next step in this program of work.